Investigation of optical core-to-core crosstalk in multicore fibers - Steinkopff, Albrecht; Aleshire, Christopher; Klenke, Arno; Jauregui, Cesar; Nold, Johannes; Kuhn, Stefan; Haarlammert, Nicoletta; Schreiber, Thomas; Limpert, Jens (Optics InfoBase Conference Papers, 2022)
We theoretically and experimentally investigate the optical cross-talk between cores of a multicore fiber. We show that the cross-talk not only depends on the numerical aperture and relative distance between the cores but also, crucially, on the size of the cores.
CRIS-Team Scopus Importer:2023-04-20